Prevalence of Work Stress on Marital Stability of Married Lecturers in University of Ilorin - Fatoye, Modupe Gbemisola; Bolu-Steve, Foluke Nike (citeus, 2025)
This study investigated the prevalence of work stress and its impact on marital stability among married lecturers at the University of Ilorin, Nigeria. A descriptive correlational survey design was employed, and 100 married lecturers were selected through a multistage sampling technique across five faculties. Data were gathered using a researcher-designed instrument titled “Work Stress and Marital Stability Questionnaire (WSMSQ),” which demonstrated strong reliability with a Cronbach Alpha coefficient of 0.81. Descriptive and inferential statistics, including Pearson Product-Moment Correlation, independent samples t-test, and one-way ANOVA, were used to analyze the data at a 0.05 level of significance. Results revealed a significant negative correlation between work stress and marital stability (r = –.426, p < .05), indicating that increased work stress is associated with reduced marital stability. However, no statistically significant differences were found in the relationship between work stress and marital stability based on gender, academic rank, or religion. These findings suggest that work-related stress affects marital relationships broadly, regardless of these demographic variables. The study recommends the establishment of faculty-based counselling services, institutional stress management policies, and marital support programs to help academic staff maintain healthy work-life balance. The study uniquely examines the marital implications of occupational stress among Nigerian lecturers, whereas prior studies have focused mainly on occupational outcomes.